1995
DOI: 10.1007/bf01289497
|View full text |Cite
|
Sign up to set email alerts
|

Yrast states in the doubly-odd nucleus100Tc

Abstract: Abstract. High spin states up to J = 14 and excitation energy up to E* = 3076 keV have been observed in the odd odd nucleus 100Tc with the reaction 96Zr(TLi, 3n), at bombarding energies between 21 and 31 MeV, by in-beam 7 spectroscopy and conversion-electron measurements.A AJ = 1 negative parity band similar to that observed in the N = 57 isotone l~ and based on the 8-, 708 keV state has been identified. The observed band can be interpreted in terms of collective core excitations based on a two-quasiparticle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…High-spin yrast states of 100 Tc were investigated using the 96 Zr( 7 Li; 3n) reaction. 31) The highest excitation energy and spin-parity reported in the study are 3,075.7 keV and 14 À , respectively.…”
Section: Level Schemementioning
confidence: 69%
See 1 more Smart Citation
“…High-spin yrast states of 100 Tc were investigated using the 96 Zr( 7 Li; 3n) reaction. 31) The highest excitation energy and spin-parity reported in the study are 3,075.7 keV and 14 À , respectively.…”
Section: Level Schemementioning
confidence: 69%
“…There were several studies which aimed at establishing low-lying levels in 100 Tc using 99 Tc(n th ; ), 22,24) 100 Mo(d; 2n), 24) 99 Tc(d; p), 27) 100 Mo(p; n), [28][29][30] and 96 Zr( 7 Li; 3n) 31 29) investigated low-lying levels of 100 Tc with the same reaction in the energy range of 4:0 E p 6:8 MeV by means ofcoincidence technique, and constructed a level scheme up to 521.0 keV. Á rvay et al 30) reported a level scheme up to 906.1 keV energy.…”
Section: Level Schemementioning
confidence: 99%
“…(1) 456.69-keV Level A level with spin-parity of 7 þ was reported at almost the same energy (457.0 keV in the original report, 31) 456.9 keV in Table 3) as this one, but the two levels seem to be different. The 456.69-keV level is populated by the 6,308.5-keV primary ray.…”
Section: ð1 þ T ðIþþ â I ðIþ; ð1þmentioning
confidence: 92%
“…31) The highest excitation energy and spin-parity reported in the study are 3,075.7 keV and 14 À , respectively.…”
Section: Level Schemementioning
confidence: 99%
See 1 more Smart Citation